Comparative Profiling of Survival, Growth, and Intestinal Microbial Community of Pearl Oyster Pinctada maxima Juvenile in the Industrial Farming: The Feasibility of Using Spray-Dried Microalgae Powder - Yang, Shouguo; Li, Xi; Vasquez, Hebert Ely; Wang, Aimin; Shi, Yaohua; Li, Jiaoni; Zhang, Xingzhi; Zheng, Xing; Gu, Zhifeng (Frontiers in Marine Science, 2022)
Industrial farming is an alternative mode for Pinctada maxima juvenile cultivation to avoid mass mortality caused by natural disasters. Suitable and enough food is crucial for successful industrial bivalves farming. To investigate the feasibility of live microalga instead by spray-dried microalgae powder in P. maxima juvenile industrial farming, the present study replaced a positive control live microalgal diet [Isochrysis zhanjiangensis (L-iso) and Platymonas subcordiformis (L-pla)] with spray-dried I. zhanjiangensis powder (P-iso) and P. subcordiformis powder (P-pla). Continuous feeding trials (30 d) were conducted on the P. maxima juvenile (1.2008 ± 0.0009 g initial weight and 30.12 ± 0.05 mm initial shell length), under laboratory condition. Survival, growth performance and intestinal microbial community were studied and compared across the groups. Results showed that survival rate (SR) did not differ significantly across the groups (ranged from 84% to 86%, P > 0.05). The growth performance in spray-dried microalga groups, including total weight (TW), shell height (SH), the absolute growth rate (AGR) and relative growth rate (RGR) for SH and TW, were slightly lower than that in live microalga groups, while the activities of pepsin (PES), amylase (AMS) and lipase (LPS) were significant higher (P < 0.05). The best growth performance was observed in L-iso group, followed by L-pla group. A 16S rRNA-based sequencing revealed that Proteobacteria was the dominant phylum in P. maxima juvenile intestinal bacteria community under controlled conditions, which accounted for 62% to 82% across groups. The intestinal bacteria at genus level were more sensitive to diets, where Burkholderia was the dominate genus both in L-iso (66.52 ±6.43%) and L-pla group (54.00 ±5.66%), while Mycoplasma, Alphaproteobacteria, Oxyphotobacteria were both in P-iso and P-pla group. The P-pla group got higher ACE, Chao1, Simpson and Shannon indices (P < 0.05). The above results suggested that the spray-dried I. zhanjiangensis powder and P. subcordiformis powder can serve as substitutes of live microalga in P. maxima juvenile industrial farming under controlled conditions.. The founding in this study provides basic data to optimize industrial farming technology and healthy management for P. maxima juvenile.